ISLAM DAN NEGARA HUKUM DI PAKISTAN (Telaah Atas Pemikiran Benazir Bhutto) - Santoso, Lukman (LP3M STAI DARUSSALAM LAMPUNG, 2012)
Pakistan is an Islamic country that became independent on August 14, 1947. Since independence, there is a difference of opinion among the Muslims of Pakistan, which consists of a group of secular, moderate Islamists and how Islam should be the application of the relation between religion and state in Pakistan, causing the prolonged political turmoil when Pakistans quest for identity in line with the will of the people and its leaders. Pakistans political crisis that was later endlessly inspiring female politicians and thinkers of Pakistan, Benazir Bhutto which is to take part in politics. Political conditions of Pakistan that full of intrigue brought on a dilemma to the meaning of the condition of Islam in Pakistan as an Islamic state.Â Keyword: Islam, Negara Hukum, Benazir Bhutto